2023
DOI: 10.53550/eec.2023.v29i01s.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Methods and Irrigation Levels on wheat (Triticum aestivum L.)

Abstract: The field experiment was carried out at agricultural research farm of IFTM University Moradabad (U.P.), India during rabi season 2018-19 to study the effect of sowing methods and irrigation levels on wheat. Sowing method and irrigation being a major constraint to reduces the potential of wheat yield. The treatments were arranged in split plot design in three replications, sowing methods in main plots and irrigation levels in sub-plots. The experiment treatments included two sowing methods, i.e. [S1 – conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Tomar et al [18] found that maximum gross return was observed in weed While the highest net monetary returns and B: C was recorded with metsulfuron-methyl 4 g/ha due to higher yield and comparatively lower cost of cultivation as compared to weed free treatment. Similar results were reported by Singh et al [19,20], Kumar et al [21] and Sahu et al [22]. The lowest gross & net returns, benefit: cost ratio, economic and production efficiency was recorded in farmer's practice.…”
Section: Effect On Cropsupporting
confidence: 87%
See 1 more Smart Citation
“…Tomar et al [18] found that maximum gross return was observed in weed While the highest net monetary returns and B: C was recorded with metsulfuron-methyl 4 g/ha due to higher yield and comparatively lower cost of cultivation as compared to weed free treatment. Similar results were reported by Singh et al [19,20], Kumar et al [21] and Sahu et al [22]. The lowest gross & net returns, benefit: cost ratio, economic and production efficiency was recorded in farmer's practice.…”
Section: Effect On Cropsupporting
confidence: 87%
“…The lowest gross & net returns, benefit: cost ratio, economic and production efficiency was recorded in farmer's practice. This was mainly owing to significantly lower yield and poor weed management in the farmer's practice [19,23,24].…”
Section: Effect On Cropmentioning
confidence: 99%